The effect of cardio exercises accompanying nutritional awareness on some anthropometric measurements of women aged (25-35) years. (Journal of the College of Basic Education, 2023)
The two researchers pointed out that the rapid invasion of technology over the years on the lives of individuals, along with the pressures of life, has led many to neglect their health. What led to a noticeable increase and weight gain over the years is that attention to health includes not neglecting exercise. The importance of the message comes from being an attempt to know the effect of cardio exercise accompanying nutritional awareness on some physical measurements for women aged (25-35) years. The researchers noted the phenomenon of weight gain, especially In women, it is widely spread, because they live a sedentary and sedentary life, rarely engage in sports activities, and do not adhere to a healthy diet to maintain body weight as a result of poor nutritional awareness, so the two researchers decided to study this problem. Body measurements for women aged (25-35) years. The two researchers used the experimental method, which depends on collecting information and data related to the research topic. The two researchers identified the research community by intentional method, and they are women aged (25-35) years who participate in fitness centers in Baghdad, and a random sample of (12) women practicing sports in the private halls of fitness centers in Baghdad was selected and the sample was chosen by random method. Physical measurements, the two researchers prepared special exercises for cardio exercises, and gave lectures on nutritional awareness with three training units per week, and included presentation, analysis and discussion of the research results. 25-35 years old.